Strategi Pemberdayaan Masyarakat dalam Sosialisasi Mitigasi Bencana Bersama BPBD Kabupaten Magelang: Mendorong Keterlibatan Aktif Masyarakat di Desa Beseran - Arista Puji Utami; Muhammad Farhan Pratama; Akbar Hajar Utama; Akbar Ade Firmansyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Beseran village is a village located inland, and faces the risk of natural disasters such as floods, landslides and strong winds. According to data from the Magelang Regency Regional Disaster Management Agency (BPBD), in 2023 there will be several natural disasters, and the biggest contributor will be landslides with a percentage of 90%. This study aims to analyze the strategies implemented to encourage active community involvement in disaster mitigation efforts. Empowerment strategies include education about disaster mitigation, preparedness training, forming disaster response groups, and developing community emergency plans. The importance of a comprehensive approach that accommodates local knowledge, specific community needs, and existing capacity is identified as a key factor in the success of empowerment programs. The methods implemented in Real Work Lecture (KKN) activities in Beseran Village in this research are observation of regional conditions, observation of activities, and preparation of work programs. The efforts made were holding a disaster mitigation socialization event which invited resource persons from the Regional Disaster Management Agency (BPBD) of Magelang Regency. Thus, this program is important to help the government and related communities in designing more effective and inclusive disaster mitigation programs, as well as contributing to building community resilience to natural disasters in the future.